Beitrag zum Vorkommen und Ausbreitung des Trauer-Rosenkäfers Oxythyrea funesta (Poda, 1761) (Coleoptera, Scarabaeidae) in Deutschland:: ein Citizen-Science-Projekt - Hoffmann, Hannes; Boetzl, Fabian A.; Medger, Gernot; Rolke, Daniel; Benisch, Christoph (Contributions to Entomology = Beiträge zur Entomologie, 2021)
The characteristic white-spotted rose beetle Oxythyrea funesta has spread rapidly in Central Europe over the past 30 years and is therefore a suitable model for Citizen Science projects. A project to document the dispersal of O. funesta in Germany was started on “kerbtier.de” in 2019 to record the species through photos uploaded by the users. 1,345 inquiries from 309 users were evaluated. Our results show that O. funesta is currently present in all regions of Germany and became a widespread and common species in the southern half of Germany. In Northern Germany, its current distribution is focused in and around the cities of Hanover, Bremen and Hamburg. In general, the species appears to benefit from climate change, as well as from the presence of sufficient flowering plants and compost heaps in urban areas where the species has been mainly documented. The suitability of Citizen-Science-projects in biodiversity research is discussed.